Platinum-Based Neoadjuvant Chemotherapy for Breast Cancer With BRCA Mutations: A Meta-Analysis - Wang, Chang-Jun; Xu, Ying; Lin, Yan; Zhu, Han-Jiang; Zhou, Yi-Dong; Mao, Feng; Zhang, Xiao-Hui; Huang, Xin; Zhong, Ying; Sun, Qiang; Li, Cheng-Gang (Frontiers in Oncology, 2020)
Background Triple-negative breast cancer (TNBC) is one of the most aggressive subtypes of breast cancer and the major phenotype of BRCA related hereditary breast cancer. Platinum is a promising chemotherapeutic agent for TNBC. However, its efficacy for breast cancer with BRCA germline mutation remains inconclusive. Here we present a meta-analysis to evaluate the effect of platinum agents for breast cancer patients with BRCA mutation in neoadjuvant setting. Materials and Methods Pubmed, Embase, and Cochrane Central Register of Controlled Trials databases were searched for relevant studies on neoadjuvant platinum treatment and BRCA related breast cancer. Fixed- and random-effect models were adopted for meta-analyses. Heterogeneity investigation was conducted by sensitivity and subgroup analyses. Publication bias was evaluated by funnel plot and Begg’s test. Results In all, five studies with 363 patients were included for meta-analysis. The pooled pathological complete response (pCR) rates were 43.4% (59/136) and 33.9% (77/227) for platinum and control groups, respectively. Adding platinum to neoadjuvant regimen did not significantly improved pCR rate (odds ratio [OR]: 1.340, 95% confidence interval [CI] = 0.677–2.653, p = 0.400). Sensitivity analyses also revealed platinum did not significantly increase pCR rate in either TNBC or HER2- patients (TNBC subgroup: OR: 1.028, 95% CI = 0.779–1.356, p = 0.846; HER2- subgroup: OR: 0.935, 95% CI = 0.716–1.221, p = 0.622). Conclusions Our meta-analysis suggested that the addition of platinum to neoadjuvant chemotherapy did not significantly improve pCR rate for patients with BRCA mutations. Further large-scale randomized control trial with survival data may provide more robust evidence on therapeutic value of platinum for breast cancer neoadjuvant treatment.